Supplier dependence asymmetry and investment in innovation: The role of psychological uncertainty. Issue 2 (March 2021) - Ma, Siqi; Hofer, Adriana Rossiter; Aloysius, John
Abstract: A key source of competitive advantage for large firms accrues from investments in innovative products and processes by their suppliers, incentivized by a positive relationship climate. A fundamental hindrance lies in a condition that commonly characterizes buyer-supplier relationships: asymmetric levels of dependence between business partners. Such asymmetry has been shown to be detrimental to the relationship, enhancing the likelihood of conflict, and negatively impacting the performance of the more dependent party. Considering that such dependence asymmetry is likely to persist, large buyers face the challenge of promoting a relationship environment that provides an incentive for suppliers to invest in innovation. In this study, we propose that large, dominant buyers can influence suppliers' intentions and behaviors by mitigating the effects of their perceived riskiness and ambiguity that emerge from a situation of dependence asymmetry. Specifically, using the lens of resource dependence theory, we investigate the effects of these two psychological dimensions of uncertainty on a supplier's trust, commitment, and willingness to invest in innovation, as well as the moderating effect of a buyer's information sharing in shaping a supplier's perceived uncertainty. The model is tested with a scenario-based experiment and results are corroborated by interviews with experienced managers of retail suppliers. Our findings indicate that a supplier's dependence on a large buyer increases its perception of ambiguity and riskiness in the relationship, negatively impacting its trust, commitment, and willingness to invest in innovation. However, a buyer who shares relevant and timely information with the supplier mitigates its perceived uncertainty, promoting the supplier's positive attitudes towards the buyer and incentivizing innovation. Sharing operational and strategic information such as point-of-sales data, sales forecasts, or strategic plans, becomes a valuable strategy to powerful buyers in the pursuit of becoming a preferred customer and enhancing a supplier's resource mobilization towards the relationship. Highlights: Dependence of a weaker party increases its perception of ambiguity and riskiness in the buyer-supplier relationship. Dependence of a weaker party negatively impacts its trust, commitment, and willingness to invest in innovation. Sharing information reduces perceived uncertainty, enhancing the attitudes, and encouraging innovation.